Dendritic morphology of motor neurons and interneurons within the compact, semicompact, and loose formations of the rat nucleus ambiguus - Fogarty, Matthew J. (Frontiers in Cellular Neuroscience, 2024)
Motor neurons (MNs) within the nucleus ambiguus innervate the skeletal muscles of the larynx, pharynx and oesophagus. These muscles are activated during vocalisation and swallowing, and must be coordinated with a great array of respiratory and other behaviours. Despite many studies evaluating the projections and orientation of MNs within the nucleus ambiguus, there is no quantitative information regarding the dendritic arbours of MNs residing in the compact, and semicompact/loose formations of the nucleus ambiguus. In female and male Fischer 344 rats we evaluated MN number using Nissl staining, and MN and non-MN dendritic morphology using Golgi-cox impregnation Brightfield imaging of transverse Nissl sections (15 µm) were taken to stereologically assess the number of nucleus ambiguus MNs within the compact and semicompact/loose formations. Pseudoconfocal imaging of golgi-impregnated neurons within the nucleus ambiguus (sectioned transverse at 180 µm) were traced in 3-D to determine dendritic arborization. We found a greater abundance of MNs within the compact compared to the semicompact/loose formations. Dendritic lengths, complexity and convex hull surface areas were greatest in MNs of the semicompact/loose formation, with compact formation MNs being smaller. MNs from both regions were larger than non-MNs reconstructed within the nucleus ambiguus. These morphological differences are consistent with the functional variation of the pharynx, larynx and oesophagus during aerodigestive behaviours.